Exploring food waste prevention through advent food consumption: The role of perceived concern, consumer value, and impulse buying - Liao, Chuanhui; Qiao, Liguang; Wang, Xuanzheng; Lu, Shanshan (Frontiers in Sustainable Food Systems, 2022)
Every year, about one third of food intended for human consumption is wasted along the distribution chain, in which advent food contributes a great portion. Advent food marketing and consumption is suggested to be a main channel to use advent food and reduce food waste. With the booming of the advent food market, it is necessary to explore the reasons for advent food purchase and food waste reduction behaviors. This study explored what consumer concerns and consumer values might influence food waste reduction intention in the context of advent food purchase. In a survey of Chinese consumers (N=509), this study develops a structure equation and tests the hypotheses with Smart-pls software. Results show that, as expected, health concern, utilitarian value, and impulse buying exert a negative effect on food waste reduction intention. A further quadratic regression was conducted, and the result indicated an inverted U relationship between economic concern and food waste reduction intention. Economic concern, utilitarian value, and hedonic value exert positive effects on impulse buying, which trigger negative influence on food waste reduction intention. Theoretical and managerial Implications and recommendations for future research are discussed.